2016
DOI: 10.12669/pjms.325.9705
|View full text |Cite
|
Sign up to set email alerts
|

Quality of drug stores: Storage practices & Regulatory compliance in Karachi, Pakistan

Abstract: Objective:To assess and evaluate the drug storage quality and regulatory compliance among privately operated drug stores of Karachi Pakistan.Methods:A cross-sectional survey of drug stores located in Karachi was conducted from May to December 2013. A total of 1003 drug stores that were involved in the sales, purchase and dispensing of pharmaceutical products were approached by non-probability purposive sampling technique, and the information was collected using a close ended, structured questionnaire.Results:O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…The maximum number of staff working in a PPMV store was three. This corroborates with findings of Shah et al among drug vendors where the majority of drug stores had between 2 and 3 staff [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The maximum number of staff working in a PPMV store was three. This corroborates with findings of Shah et al among drug vendors where the majority of drug stores had between 2 and 3 staff [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that a high proportion of the PPMVs stored anti-malarial medications in acceptable storage conditions as similarly documented by ACT watch Group in an outlet survey conducted in Nigeria [ 23 ]. Nearly all stores’ anti-malarials were stored in a dry area place within the stores, stored out of reach of children, protected from direct sunlight, the PPMVs’ stores had washable floors and the majority of the stores had tidy floors since anti-malarial medicines were not kept on the floor rather they were stored on shelves which varies completely from the result obtained by Shah et al among drug stores owners in Pakistan where anti-malarial medicines were stored directly on the floor which made the stores untidy [ 16 ]. Storage of anti-malarial medications in acceptable storage conditions can be attributed to the PPMVs association, the Nigerian Association of Patent and Proprietary Medicine Dealers (NAPPMED) who occasionally check on the members’ practices to monitor their adherence to guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is struggling with a number of threats to the optimal use of medicines, including high prevalence of medication errors (causing deaths of 0.5 million people annually [13]) and adverse drug reactions (detected in 60% adults and 40% children [14]), misuse of controlled substances (by 6.7 million individuals [15]), and excessive self-medication [16]. There is also a growing list of medicine-related issues that demand immediate participation of pharmacists in the patient's welfare, including over-the-counter (OTC) availability of prescription medicines, inappropriate use of medicines, formulation issues, unsafe storage and disposal of medicines, and poor availability of medicines [16][17][18][19][20][21]. Additionally, poor health in the female population, elderly, and medically underserved rural populations in Pakistan need scalable and affordable community pharmacy services, such as health screening (e.g., diabetes, cholesterol, osteoporosis), timely immunizations, pain control, and home-based care delivery and family planning services [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, the private sector makes up the predominant proportion of health care system. Most pharmacies are also in the private sector [10,12,13,14,15,16]. There are more than 80,000 community pharmacies in Pakistan [11].…”
Section: Introductionmentioning
confidence: 99%
“…The legal licensing requirements are not fulfilled. The overall practices are unsatisfactory, due to unqualified supervision [12,13,14,15,16]. The practices and services of urban pharmacies are considered better than those of pharmacies in rural areas [10].…”
Section: Introductionmentioning
confidence: 99%